Reinforcement evaluation with external pretension of Marcelino Machado bridge, highway BR-135, São Luís – MA - Nolasco, Ana Caroline Pereira; Rodrigues, Clésio de Oliveira; Silva, Debora Emylle Carvalho; Matos, Debora Ferreira; Silva, Helde Costa; Sá, Julianne Ferreira de; Santos, Marly Cirqueira; Gomes, Randal Silva; Reis, Thalyta Souza; Bonjardim, Witor Carvalho (Seven Editora, 2023)
External pretension is one of the existing structural reinforcement methods and is widely used in cases of reinforcements in bridges, including in Brazil, due to the possibility of actively strengthening the structure without the need to change its original section and interrupt its use during the work. The objective of this research is to analyze the structural reinforcement method using the pretension of the steel cord, with hydraulic jacks, used for the recovery and reinforcement of the structure of the Marcelino Machado bridge, in São Luís - MA. The methodology of the study can be divided into two stages: The evaluation of the revitalization and recovery of the bridge through the structural projects used in the reform and the photos of the execution, as well as through the literature review of the advisory literatures that add knowledge to the theme addressed. Thus, throughout the work, the methods for the execution of structural reinforcement through pretension were approached, in which the mechanism helps to annul the presence of pathologies on the bridge that may compromise the structure. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-119